Integrated analysis of transcriptomics and metabolomics and high-throughput amplicon sequencing reveals the synergistic effects of secondary metabolites and rhizosphere microbiota on root rot resistance in Psammosilene tunicoides - Yingtao, Li; Qiaofeng, Li; Lijuan, Wang; Shuyun, Qi; Zhou, Jiang; Wenping, Zhang; Aili, Zhang (Frontiers in Microbiology, 2025)
Psammosilene tunicoides is a plant with significant medicinal and ecological value, exhibiting remarkable medicinal properties, particularly in anti-inflammatory, antioxidant, and immune-regulatory effects. Root rot is one of the primary diseases affecting Psammosilene tunicoides, leading to a significant decline in its quality. In this study, we utilized an integrated analysis of transcriptomics, metabolomics, high-throughput amplicon sequencing, and culturomics for revealing the difference of healthy samples (CH) and diseased samples (CD) and studying the defense mechanism of P. tunicoides in resisting root rot. Transcriptome revealed distinct patterns of gene expression between healthy root samples (HR) and diseased root samples (DR) of P. tunicoides. The Key enzyme genes involved in triterpene (e.g., HMGS, DXS, SQS, CYP450) and flavonoid (e.g., PAL, CHS, CHI) biosynthesis pathways were significantly upregulated in DR. Consistent results were observed in the metabolomic analysis, where triterpene saponins and flavonoids were more highly accumulated in DR than in HR. Microbiome data indicated a significant enrichment of Actinobacteria at the genus level in the rhizosphere soil of diseased samples (DS) compared to healthy samples (HS) while the mostly beneficial growth-promoting bacterial groups were found in DR root endophytes, including Enterobacter, Pseudomonas, Klebsiella, Stenotrophomonas, and Bacillus. Through culturomics, we successfully isolated and identified over 220 bacterial strains from the rhizosphere soil of diseased samples, including genera including Bacillus, Streptomyces, Cupriavidus, Pseudomonas, and Paenarthrobacter. Notably, the strain Pseudomonas sp., which was significantly enriched in DR, exhibited a clear antagonistic effect against Fusarium oxysporum. Co-occurrence network analysis of multi-omics data revealed that many Actinomycetes positively correlated with triterpenoid and flavonoid compounds and their key genes. Therefore, we conclude that these secondary metabolites may could resist pathogen invasion directly or serve as an “intermediate medium” to recruit growth-promoting microorganisms to resistant the root rot. This study investigates the “Plant-Microbe” interaction network associated with root rot resistance in P. tunicoides, revealing its significant implications for the ecological cultivation and management of this species.